Students’ Perceptions of Course Syllabi: The Role of Syllabi in Motivating Students - Wheeler, Lindsay B.; Palmer, Michael; Aneece, Itiya (International journal for the scholarship of teaching and learning, 2019)
In this mixed methods study, researchers explored students' perceptions of different types of syllabi, the course, and the instructor articulated through the syllabi. Students were randomly assigned to read one of two US History syllabi: a content-focused syllabus (CFS), characterized as a traditional, content-focused, policy-laden syllabus; or a learning-focused syllabus (LFS), characterized by strong learning objectives, authentic assessments, and a positive, motivating tone. Results show that LFS participants (n=61) had significantly more positive perceptions of the document, the course, and the instructor described by the document than CFS participants (n=66). LFS participants found, for example, more of the syllabus components to be useful, anticipated more student involvement in class, expected to learn more useful concepts and skills, and anticipated that the instructor would help them be successful. Although additional research is needed to determine generalizability of these results, we conclude that instructors have little to lose and much to gain by creating a learning-focused syllabus.